ANALISIS PENDAPATAN UMKM (Studi Kasus Java Fiber Banjardowo Jombang) - Siti Nur Qomariyah; Mukhibatul Khusnia (MARGIN ECO, 2021)
Business feasibility analysis is carried out to help Java Fiber business see the feasibility of the business so that it is feasible to be developed. This study aims to analyze: the structure of business production costs in Java Fiber, operating income in Java Fiber, Business Feasibility in Java Fiber. This research was conducted in Jombang District, Jombang City, from February to June 2021. The method used in this research is a survey method. The data collected includes secondary data and primary data. The primary data was obtained by direct interviews with the Java Fiber business owners, while the secondary data was obtained from books and financial reports. Analysis of the data used is an analysis that includes the structure of production costs, income, business feasibility in Java Fiber, Jombang District, Jombang City. The results showed that the structure of the production cost of a 5-month business with an average fixed cost of Rp. 1,987,500, variable costs Average Rp. 124.918.850, total cost Rp. 126,906.350 , the average value of 5 months from the revenue of Java Fiber business is Rp. 216,712,700. while the net income of 5 months of Java Fiber Banjardowo Jombang's business is Rp. 89,806.350. The feasibility of Java Fiber Banjardowo, Jombang District, Jombang City can be said to be feasible to be cultivated with an R/C Ratio value of 1.71. Keywords : Java Fiber business, production costs, revenue, business feasibility.